MEMES AS POWERFUL SYMBOLS OF COMMUNICATION IN THE DIGITAL ERA - Djumabаyeva Mokhira Anvardjanovna (Modern American Journals, 2025)
This article is devoted to the role of internet memes as a form of modern hieroglyphic communication, analyzing their function as culturally loaded visual symbols in the digital age. Drawing parallels between ancient pictographic systems and contemporary digital media, the study investigates how memes transcend linguistic barriers to convey complex ideas, emotions, and social commentary. It also examines how memes shape and reflect cultural identities, influence discourse, and serve as tools of both unity and division.
Keywords: Communicative symbols, digital culture, social platforms, digital communication, phenomenon, social narratives.